The Relationship of Academic Supervision and Managerial Supervision in Vocational High Schools - Kholil, Muhamad; Harahap, Nasruddin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aims to determine the relationship between academic supervision by the Headmaster in improving teacher performance and the relationship between managerial supervision by the Headmaster in increasing Headmaster competence. This research is a quantitative research using ex-post-fact research methods. The population of this study was Headmaster of vocational schools in East Ogan Komering Ulu Regency and supervisors. The sample collection technique used random sampling techniques. The samples used in the research were 20 headmasters and 20 vocational school supervisors in the East OKU district. The data collection technique uses a questionnaire. The data source uses primary data. Data analysis uses prerequisite test analysis and hypothesis testing using the product-moment correlation test. Based on the results of the data analysis, the results showed that there was a significant relationship between academic supervision by the Headmaster and teacher performance. This can be seen from the correlation coefficient of the two variables, namely 0.020. Furthermore, there is a significant relationship between managerial supervision by the supervisor and the competence of the Headmaster, which can be seen from the correlation coefficient of the two variables, namely 0.596. The relationship and link between supervisory supervision, Headmaster competence, Headmaster supervision, and teacher performance are very important in maintaining and improving the education quality in a school. Thus, healthy relationships and good links between supervisory supervision, Headmaster competence, Headmaster supervision, and teacher performance are very important to achieving better quality education in a school.